Semiotics Analysis of 'Gemoy' Animations Political Communication Strategy in Efforts to Change Prabowo-Gibran's Branding - Yarnis, Yarnis; Muksin, Nani Nurani (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2024)
This research will focus on the symbolic interaction of the 'gemoy' character carried by the Prabowo-Gibran pair. This research uses a qualitative research method that uses a literature review by using various data and information about the "gemoy" character found in the media, both print and digital media. The data analysis used is semiotic analysis to analyze the meaning behind the 'gemoy' branding used by Prabowo-Gibran. The results of the study found that the political campaign strategy used by Prabowo-Gibran has a message meaning that the winning team is trying to show another character from Prabowo to attract the attention of young voters. The viral animated character also indirectly disguises Prabowo's figure who has been considered tough because he is a former military man. Therefore, many young voters on several social media accounts showed their support for Prabowo-Gibran by uploading 'gemoy' animated content. The purpose of this research is to find out in more detail the implied meaning of the characters used by the Prabowo - Gibran winning team. This can be a reference for various parties in the future to be able to use unique ways of campaigning that might get a lot of votes from the public. What Prabowo-Gibran has done is almost the same as what Ferdinand Marcos Jr. did. Therefore, the use of unique ways to campaign is one of the positive political strategies to attract public attention. In addition, the results of this study are so that readers can understand that various kinds of political strategies can coexist with the vision and mission of the presidential and vice presidential candidates.